PERTUMBUHAN EKONOMI, KONSUMSI ENERGI TERBARUKAN, DAN EMISI KARBON - Ronaldi Defastian Ronaldi Defastian (GREET, 2026)
This study examines the relationship between economic growth, renewable energy consumption, and carbon emissions by explicitly accounting for income-level heterogeneity and nonlinear growth dynamics. Using panel data from [xx] countries over the period [tahun–tahun], this study employs fixed effects and dynamic panel estimators within the Environmental Kuznets Curve (EKC) framework to capture both unobserved heterogeneity and dynamic adjustment processes. The results indicate that renewable energy consumption has a statistically significant negative effect on carbon emissions, confirming its role in mitigating environmental degradation. Economic growth exhibits a nonlinear relationship with emissions, supporting the EKC hypothesis. Importantly, the emission-reducing impact of renewable energy is found to be substantially stronger in high-income countries than in middle- and low-income economies, highlighting pronounced heterogeneity across development stages. These findings suggest that renewable energy contributes more effectively to the decoupling of economic growth from carbon emissions when supported by adequate infrastructure, institutional capacity, and technological readiness. The study provides novel empirical evidence on the differentiated role of renewable energy in sustainable development and offers important policy implications for designing income-specific energy transition strategies.